Implementation Of The Six-Day Work Policy And Its Impact On Employees' Work-Life Balance (A Study at the SAMSAT Office of Sukadana, East Lampung) - Ni Putu Widhia Rahayu; Azah Rawan Sangun (Cita konsultindo, 2026)
This study aims to analyze the implementation of the six-day work policy (work policies) and its impact on employees' work-life balance at the SAMSAT Office of Sukadana, East Lampung. The research employed a qualitative approach using interviews, observation, and documentation methods. Data analysis was conducted using qualitative analysis techniques. The findings indicate that the six-day work policy at the SAMSAT Office of Sukadana, East Lampung, has been implemented in a structured manner through work schedule arrangements, task distribution, and coordination among employees to maintain the quality of public services. Employees' perceptions of this policy vary; while improved public service is viewed positively, the policy also has the potential to disrupt employees' work-life balance. The implementation of the policy is supported by leadership commitment, employee discipline, and a well-coordinated work system; However, it also faces obstacles such as increased workload, limited rest time, and the risk of physical and psychological fatigue. The six-day work policy has implications for employee welfare and organizational productivity, thus requiring optimal management to enhance service effectiveness without compromising employee satisfaction and well-being.